THE EFFECT OF FISHBOWL STRATEGY IN SPEAKING ABILITY FOR THE SECOND YEAR STUDENTS OF SMPN 1 TERARA IN THE SCHOOL YEAR 2022-2023 - Ahmad Zuhri Rosyidi; Atika Salman Paris (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
Fishbowl strategy is extremely significant strategy in teaching speaking skill especially English for the language learners. This study focus on finding the effect of fishbowl strategy in teaching speaking ability for the eighth grade students of SMPN 1 Terara in the school year 2023. This study was an experimental research. The population of this study was all the the eighth grade students of SMPN 1 Terara in the school year 2020. The sample of this study was 32 students. In collecting the data, this study used speaking test instrument. Then, to analyze the data this study used descriptive statistic and testing hypothesis. The result of this study found that the mean score of experimental group was 41.2 and for the control group was 40.5. In testing the hypothesis was found that t-test was 2.948 and t-table in significant rank 5% was 2.10 (2.948 > 2.10), those founding means that the hypothesis was accepted. It means that there is an effect of fishbowl strategy toward speaking ability and the students.